Level of professional Burnout among family physicians in the Republic of Moldova and certain aspects regarding its contributing factors (One Health & Risk Management, 2025)
Introduction. Family medicine represents a key component of the healthcare system, a specialty characterized by fragmented work, high demands from patients/families/communities, and often conflicting interactions, all of which are conditions that predict stress and the onset of burnout. The aim of this study was to assess the degree to which family physicians in the Republic of Moldova are affected by professional burnout, as well as to identify its determining factors.Materials and methods. The research was conducted as a descriptive cross-sectional study from November 2023 to February 2024, on a sample of 352 family doctors.Results. The results show that 100% of family physicians were affected by professional burnout. The most prominent dimension of the burnout syndrome was psycho-emotional exhaustion, with a high level identified in 45.5% of respondents. Family physicians in the younger age group (36-45 years) were more affected by burnout. Family physicians working in urban areas were more affected than those in rural areas. According to the respondents, professional factors were the main contributors to the development of burnout syndrome.Conclusions. The professional burnout syndrome was identified in all family physicians involved in the study, with the dimension of psycho-emotional exhaustion being the factor with the greatest impact.